(untitled)
Some new mixed ligand complexesof zirconium (IV)containing 1,2diarninocyclohexane NNN’ N’ tetra-acetic acid (DCTA) andsome monodentatc organic ligands havebeensynthesizedandcharacterized. Complexes of thorium (IV) and uranium (VI) containing OCTA only have also been reported here. OCTA behaves as a hexadentate, quadrinegative ligand in all the zirconium, thorium and uranium complexes. Zirconium and uranium complexes are presumably seven and eight-coordinated respectively whereas thorium complex is octahedral. The complexes have thecompositions: [Zr(OCTA)L